Wednesday
March 29, 2017

Post a New Question

Posted by on .

(-2x^2y)^3*(5xy^3)^2=(-2x^2y)^3 = -8 x^6 y^3
*Is this correct.?

(-2x^2y)^3 * (5xy^3)^2 =

(-8x^6y^3) * (25x^2y^6) =

-200x^8y^9

When you have the same base, you add exponents when multiplying. For example, x^2 * x^3 = x^5.

When you have the same base, you multiply exponents when you have something like (x^2)^3. This would be x^6.

I hope this will help.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question